Comprehensive genome data analysis of Pseudomonas benzopyrenica Ch9-16 Isolated from chili powderNational Center for Biotechnology Information - Mayra Paola Mena Navarro; Merle Ariadna Espinosa Bernal; Ana Laura Vega Rodríguez; Daniel Alejandro Ferrusca Bernal; Juan Enrique de Jesús López; María Carlota García Gutiérrez; Karla Isabel Lira de León; Miguel Angel Ramos López; Aldo Amaro Reyes; José Alberto Rodríguez Morales; Héctor Pool; Carlos Guzmán Martínez; et al. (Data in Brief)
We provide a comprehensive genome analysis of Pseudomonas benzopyrenica Ch9–16, a bacterial strain isolated from chili powder processed in Fresnillo, Zacatecas, Mexico. The genome was sequenced using the Illumina NovaSeq platform. Bioinformatic analyses, including assembly and annotation, were conducted on the BV-BRC platform. The genome, comprising 18 contigs and approximately 5.3 million base pairs with a GC content of 65.19 % and 4854 protein-coding sequences. Analysis identified multiple antibiotic resistance genes (ARGs) and virulence genes. This genome data serves as a valuable resource for understanding this bacterial specie and contributes to the database of microorganisms isolated from chili powder. The genome data was deposited at National Center for Biotechnology Information (NCBI) under accession number Bioproject ID PRJNA1062060, Bio Sample ID SAMN45486407. The genome accession number was JBLHDL000000000.